Analisis Kandungan Formalin Pada Mi Basah di Pasar Tondano dengan Spektrofotometri UV-Vis - Fitriani, Fitriani; Palilingan, Septiany Christin; Saiya, Abdon (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2026)
Food safety is a critical aspect in protecting the public from hazardous contamination. Wet noodles have a relatively short shelf life, making them susceptible to misuse through the addition of formaldehyde as a preservative. This study aimed to qualitatively identify the presence of formaldehyde and to provide a preliminary estimation of its concentration in wet noodles sold at Tondano Market. Qualitative analysis was conducted using potassium permanganate (KMnO₄), while quantitative analysis was performed indicatively using UV–Vis spectrophotometry with chromotropic acid reagent at a wavelength of 520 nm. The results indicated that all samples were positive for formaldehyde. The detected concentrations were 54.01 mg/kg, 35.82 mg/kg, and 26.43 mg/kg, respectively. The presence of formaldehyde in all samples indicates a violation of food safety regulations and poses potential health risks to consumers. These findings highlight the need for stricter monitoring of wet noodle distribution in traditional markets.